2020
DOI: 10.3934/nhm.2020025
|View full text |Cite
|
Sign up to set email alerts
|

Micro- and macroscopic modeling of crowding and pushing in corridors

Abstract: Experiments with pedestrians revealed that the geometry of the domain, as well as the incentive of pedestrians to reach a target as fast as possible have a strong influence on the overall dynamics. In this paper, we propose and validate different mathematical models at the micro-and macroscopic levels to study the influence of both effects. We calibrate the models with experimental data and compare the results at the micro-as well as macroscopic levels. Our numerical simulations reproduce qualitative experimen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The analysis casts doubt on the initial claim that the dynamics cannot be explained without social psychology, as social behaviour like queuing norms could not be detected. By contrast, a theoretical study based on simulations with a cellular automata model [ 18 ] found some indications for an increasing density. However, due to the discrete nature of cellular automata and the resulting coarse (spatial) resolution, the microscopic interactions and emergent phenomena could not be studied in sufficient detail.…”
Section: Introductionmentioning
confidence: 91%
“…The analysis casts doubt on the initial claim that the dynamics cannot be explained without social psychology, as social behaviour like queuing norms could not be detected. By contrast, a theoretical study based on simulations with a cellular automata model [ 18 ] found some indications for an increasing density. However, due to the discrete nature of cellular automata and the resulting coarse (spatial) resolution, the microscopic interactions and emergent phenomena could not be studied in sufficient detail.…”
Section: Introductionmentioning
confidence: 91%
“…Bottleneck flow is one of the central problems in pedestrian dynamics and has been studied extensively both experimentally [6,[14][15][16][17][18][19][20][21][22][23][24][25] and theoretically [13,[26][27][28][29][30][31][32][33][34]. Here an important factor is the motivation of the individuals to reach their target.…”
Section: Introductionmentioning
confidence: 99%
“…For low motivation and narrower corridors, distinct lanes form in the corridor which can disappear in the high motivated scenario, or by widening the bottleneck. A numerical and analytical study was conducted on the phenomena using a cellular automata model [26] where the effects of the increasing density are hinted at. However, through the limited spatial resolution cellular automata models cannot capture all details.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, [17], the friction parameter was extended to a function of the number of agents in clogging for a more realistic result of the pedestrian outflow through the exit. The effect of queuing and pushing behavior in front of the bottleneck on the overall dynamics of the crowd is explored using another CA model in [18], where a local pushing mechanism is used [19]. Another global pushing mechanism is proposed in [20].…”
Section: Introductionmentioning
confidence: 99%